2019
DOI: 10.1101/567867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MRI and cognitive scores complement each other to accurately predict Alzheimer’s dementia 2 to 7 years before clinical onset

Abstract: Background:Predicting cognitive decline and the eventual onset of dementia in patients with Mild Cognitive Impairment (MCI) is of high value for patient management and potential cohort enrichment in pharmaceutical trials. We used cognitive scores and MRI biomarkers from a single baseline visit to predict the onset of dementia in an MCI population over a nine-year follow-up period. Method:All MCI subjects from ADNI1, ADNI2, and ADNI-GO with available baseline cognitive scores and T1w MRI were included in the st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In our previous work, we showed that when predicting onset of dementia in subjects with mild cognitive impairment, MRI-based features (SNIPE) are more sensitive compared to cognitive features, and even more so with longer follow-up periods, while cognitive features contribute more to the specificity of the prediction [15]. Here, we also show that cognitive features lose sensitivity when it comes to predicting cognitive decline at 36 months compared to that at 24 months.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In our previous work, we showed that when predicting onset of dementia in subjects with mild cognitive impairment, MRI-based features (SNIPE) are more sensitive compared to cognitive features, and even more so with longer follow-up periods, while cognitive features contribute more to the specificity of the prediction [15]. Here, we also show that cognitive features lose sensitivity when it comes to predicting cognitive decline at 36 months compared to that at 24 months.…”
Section: Discussionsupporting
confidence: 55%
“…At three years, prediction sensitivity of MOCA and ADAS dropped to 66.4%, but adding HC SNIPE features raises it to 75.4%, a 9% increase. As we have previously shown [15], MRI-driven features help contribute more sensitivity to the prediction at later followup periods. Despite the fact that predicting subtle cognitive decline is harder than predicting conversion from MCI to AD, the predictive accuracy of cognitive decline remains high.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…These processing methods have previously shown patterns of atrophy in cognitively normal, MCI, dementia, and neurodegenerative disease populations, including ADNI (37)(38)(39)(40). These techniques thus have the required sensitivity to reveal group differences between SCD-and SCD+.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the role of ADAS-Cog scores in the evaluation of AD, as well as the relationship between ADAS-Cog and MRI ( [25]- [30], [66], [67]). For instance, Wang et al [66] proposed a multitask exclusive relationship learning model to automatically capture the intrinsic relationship among tasks at different time points for estimating clinical measures based on longitudinal imaging data.…”
Section: Discussionmentioning
confidence: 99%